Design Of Individual Educational Trajectories In Adult Education Based On Artificial Intelligence Technologies - Feruza Rahmatullayevna Norboyeva (Periodica Journal, 2025)
The article covers the issues of designing individual educational trajectories in adult education based on the use of artificial intelligence technologies in the modern educational system.nnotation: the article covers the issues of designing individual educational trajectories in adult education based on the use of artificial intelligence technologies in the modern educational system. The study analyzes the theoretical foundations of the andragogical approach, the role of artificial intelligence technologies in the educational process, and the mechanisms for organizing personality-oriented education. The results of the study serve to improve the effectiveness of adult education
Keywords: adult education; andragogy; individual educational trajectory; adaptive education